If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + 5 = 2x Combine like terms: 13 + 5 = 18 18 = 2x Solving 18 = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 18 + -2x = 2x + -2x Combine like terms: 2x + -2x = 0 18 + -2x = 0 Add '-18' to each side of the equation. 18 + -18 + -2x = 0 + -18 Combine like terms: 18 + -18 = 0 0 + -2x = 0 + -18 -2x = 0 + -18 Combine like terms: 0 + -18 = -18 -2x = -18 Divide each side by '-2'. x = 9 Simplifying x = 9
| -5(8n-6)=-34-8n | | -8(1+4b)=20-4b | | x^2-3x=-18 | | 10*x=20 | | =6sinx | | 9x^3-21x^2-18x=0 | | 40x^2-18x+2=0 | | -n^2-8n-31=0 | | 30x^2-22x+4=0 | | (3y-7)=-7y+19 | | y=3x^2-6x-7 | | 14.99x-2.5=13.49x-1 | | 5x+20y=900 | | 7p-26=-22+9p | | 48x+8= | | 35x+7= | | Y=x^3+7 | | (x-2y)dx+(y-2x)dy=0 | | (1-u)(5u-9)=0 | | 3(6m)+m= | | 3x^3+x^2-9x-3=0 | | 5x^3-x^2-5x+1=0 | | x-49=47 | | 3=e^7x | | 3log(x)-x=0 | | 3ln(x)-x=0 | | y=4x^2-4x^2-12x+9 | | [-x-3(x-3)]= | | y=-x^2-12x+9 | | -4x-3=-5-2x | | z=5x+3y | | 100=P(0.015) |